2004
DOI: 10.1016/j.sna.2003.09.045
|View full text |Cite
|
Sign up to set email alerts
|

An electromagnetic, vibration-powered generator for intelligent sensor systems

Abstract: This paper describes the design of miniature generators capable of converting ambient vibration energy into electrical energy for use in powering intelligent sensor systems. Such a device acts as the power supply of a microsystem which can be used in inaccessible areas where wires can not be practically attached to provide power or transmit sensor data. Two prototypes of miniature generator are described and experimental results presented. Prototype A is based around two magnets coupled to a coil attached to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
307
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 649 publications
(310 citation statements)
references
References 4 publications
0
307
0
3
Order By: Relevance
“…A number of authors have considered electromagnetic vibration energy harvesters ranging from micro electro mechanical (MEM) devices [75−78] to larger scale devices with dimensions of the order of a few centimetres [42,79] . A range of material combinations and magnet/coil configurations have been considered in research devices and a limited number of commercial units developed [80] .…”
Section: Electromagnetic Conversionmentioning
confidence: 99%
“…A number of authors have considered electromagnetic vibration energy harvesters ranging from micro electro mechanical (MEM) devices [75−78] to larger scale devices with dimensions of the order of a few centimetres [42,79] . A range of material combinations and magnet/coil configurations have been considered in research devices and a limited number of commercial units developed [80] .…”
Section: Electromagnetic Conversionmentioning
confidence: 99%
“…The first configuration consists of two magnets, Fig. 1(a) while the second configuration, Fig 1(b) consists of four magnets [5]. Neodymium Iron Boron magnet was used in his design.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the second configuration is able to generating useful power and voltage levels from ambient vibrations. An average power of 157 µW is obtained when a similar device described mounted on the engine block of a car [5]. This paper will investigate different configurations of electromagnetic generator via FEA.…”
Section: Introductionmentioning
confidence: 99%
“…They reported 1 mW of power generated for a 0.24 cm 3 volume at a frequency of 320 Hz. Further, Glynne-Jones et al [4] demonstrated working of an assembled electromagnetic power generator, using fixed bulk magnets and moving wire-wound coil fixed on a stainless steel beam. The generator produced a power of 180 W at a frequency of 322 Hz, acceleration of 2.7 m/s 2 and had a volume of 0.84 cm 3 .…”
Section: Introductionmentioning
confidence: 99%